Yarrowia lipolytica possesses two plasma membrane alkali metal cation/H+ antiporters with different functions in cell physiology - Papouskova, Klara; Sychrova, Hana (FEBS letters, 2006)
The family of Nha antiporters mediating the efflux of alkali metal cations in exchange for protons across the plasma membrane is conserved in all yeast species. Yarrowia lipolytica is a dimorphic yeast, phylogenetically very distant from the model yeast Saccharomyces cerevisiae. A search in its sequenced genome revealed two genes (designated as YlNHA1 and YlNHA2) with homology to the S. cerevisiae NHA1 gene, which encodes a plasma membrane alkali metal cation/H+ antiporter. Upon heterologous expression of both YlNHA genes in S. cerevisiae, we showed that Y. lipolytica antiporters differ not only in length and sequence, but also in their affinity for individual substrates. While the YlNha1 protein mainly increased cell tolerance to potassium, YlNha2p displayed a remarkable transport capacity for sodium. Thus, Y. lipolytica is the first example of a yeast species with two plasma membrane alkali metal cation/H+ antiporters differing in their putative functions in cell physiology; cell detoxification vs. the maintenance of stable intracellular pH, potassium content and cell volume.
Keywords: Protein Transport; Time Factors; Sodium; Yarrowia; časové faktory; sodík; antiportéry; Sequence Analysis, Protein; exprese genu; Fungal Proteins; buněčná membrána; Salts; sekvenční analýza proteinů; Potassium; fungální proteiny; Antiporters; rekombinantní fúzní proteiny; Gene Expression; transport proteinů; draslík; Cell Membrane; Saccharomyces cerevisiae; Recombinant Fusion Proteins; soli